Inclusive Science: Inspiring 8th Graders from Underrepresented Groups to Embrace STEM with Microbiology and Immunology - Desmin N. Shoemaker (American Society for Microbiology, 2020)
Inclusivity in STEM requires practices that include transforming the culture in a classroom. This can be done not only by placing value on diversity but also by providing an engaging student experience, instilling a sense of belonging, and encouraging students at all levels to use a critical lens to solve problems. As a way to develop an inclusive science curriculum for students in a community that is among the poorest in New York state, local STEM organization Rise High Inc. partners with experts in STEM fields, K–12 educators, mentors, and community organizations to create sustainable low-cost, high-quality, engaging, and relevant content that sparks curiosity and exploration for this underserved community. The educators and mentors also have a unique opportunity to develop self-awareness about their own pathways and how they can use their experiences to enrich the classroom. An exemplary case is this highly interactive two-part instructional module in Microbiology and Immunology, which targets 8th graders and was designed in partnership with a local expert in these fields. This module offers creative means to learn and apply knowledge in realistic ways, while using easy-to-access materials in classrooms.